Assessment on CPR Knowledge and AED Availability in Saudi Malls by Security Personnel: Public Safety Perspective. (13th April 2020) - Al Haliq, Samer A.; Khraisat, Omar M.; Kandil, Mohamed A.; Al Jumaan, Mohammed A.; Alotaibi, Faris M.; Alsaqabi, Fahad S.; Alajmi, Hussain M.; Ellouly, Hany A.; Al-Haliq, Mahmoud A.; Alkhawaldeh, Abdullah; ALBashtawy, Mohammed; Abuhammad, Sawsan H.
Abstract : Security personnel are the first ones who attend the scene in the case of out-of-hospital cardiac arrest (OHCA) at malls. Cardiopulmonary resuscitation (CPR) is not enough for those patients; they need an automated external defibrillator (AED) to bring the heart to function normally. This study aimed to assess the current status of CPR and AED knowledge and availability in Saudi malls by security personnel. Using a descriptive design, a study was conducted at seven malls located in the Eastern Province of Saudi Arabia. Two hundred and fifty participants were surveyed using the American Heart Association (AHA) 2015 guidelines to assess CPR and AED knowledge and availability in Saudi malls. The sample mean age was 32.60 years (SD = 10.02), and 87% of participants were working as security personnel. The majority of the participants had not received training about CPR and AED (75.8% and 95.2%, respectively). Common misconceptions are fallen into all categories of CPR and AED knowledge. Correctly answered statements ranged from 7.2% in the compression rate to 24.2% in hand placement. The study results indicated a poor training knowledge of CPR and AED in public settings. Integrating high-quality CPR and AED knowledge within the school and college curricula is a vital need. However, in order to maximize the survival rate, it is important to set laws and legislation adopted by stakeholders and decision makers to advocate the people who try to help, mandate AED installation in crowded places, and mandate teaching hands-only CPR and AED together as a package.